Quality and consumer preferences on Gayo Arabica coffee brew based on the blending formulation and brewing method [Mutu dan konsumen terhadap seduhan kopi Arabika Gayo berdasarkan formulasi pencampuran bubuk kopi dan metode penyeduhan] - Hasni, Dian; Hidayanti, Nori Asri; Rahmany, Mahathir; Widayat, Heru Prono; Muzaifa, Murna; Rahmad, Dedy (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Gayo Arabica coffee has three cultivars that farmers in the Gayo Highlands commercially manage: Timtim, Borbor, and Ateng Super. Coffee blending is necessary to optimize the quality of Gayo Arabica coffee brews. In addition to the blend formulation, the brewing method also affects the quality of the brew. This study aims to understand the quality of coffee brews and consumer acceptance of two blending formulations optimized from previous research, brewed using four different brewing methods. The research used a factorial randomized block design with two factors. The first factors were the Gayo coffee blend formulation, 25% Timtim + 50% Borbor + 25% Ateng Super and 50% Borbor + 50% Ateng Super. The second factor was the coffee brewing method consisting of 4 levels: manual brew, French press, V60, and espresso. Brew quality parameters included pH, total dissolved solids, antioxidant activity, and sensory attributes such as aroma, flavor, body, aftertaste, and overall. The results showed that the interaction between the coffee blend formulation and the brewing method did not significantly affect the flavor in the sensory test. The coffee blend formulation significantly affected aroma, aftertaste, body, and overall but did not significantly affect antioxidant activity (65.87-65.42%), total dissolved solids (1.35°Brix), and pH. The Simple Additive Weighing method ranking test indicated that the best treatment combination was found in the formulation of 25% Timtim + 50% Borbor + 25% Ateng Super brewed using the French press method.